530PPrognostic value of C-reactive protein, albumin and C-reactive protein to albumin ratio in small cell lung cancer: A meta-analysis. (24th November 2019) - Barbon, C E; Velasco, R; Sacdalan, D B L; Angeles, R R
Abstract: Background: Recent evidence have showed that high level of systemic inflammation is associated with poor survival in patients with malignancy by promoting cell proliferation. Inflammation-based serum biomarkers including C Reactive Protein (CRP), Albumin (ALB) and CRP/ALB ratio have been showed to have prognostic value in patients with Small Cell Lung Cancer (SCLC). C-reactive protein (CRP) is a nonspecific serum marker of acute-phase inflammatory response. Studies have hypothesized that High CRP is a surrogate marker of tissue inflammation secondary to tumor growth. Albumin is both an inflammatory and nutritional marker. They are readily available and cost-effective tests that are potential prognostic biomarkers and therapeutic targets. Prognostic biomarkers help to optimize therapy decisions, as they provide information on the likelihood of response to a given chemotherapeutic regimen. Methods: The databases of PubMed, Cochrane, and Google Scholar were systematically searched until July 2019. Associations between CRP, ALB and CRP/ALB ratio and overall survival (OS) were investigated by pooling hazard ratio (HR) and 95% confidence interval (CI). Results: A total of 13 studies comprising of 2, 034 patients were included. The results showed that only High CRP (HR 1.36, CI 95% 1.01, 1.82 p = 0.04) and High CRP/ALB (HR 1.38, CI 9%% 1.15, 1.64 p = 0.0004) ratio are significantly associated with overall survival. Albumin has no statistical association with OS. Conclusions: High CRP and CRP/ALB ratio are independent prognostic biomarkers in patients with SCLC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.